1999
DOI: 10.1046/j.1365-2664.1999.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of changing the season in which cereals are sown on the diversity of the weed flora in rotational fields in Denmark

Abstract: Summary 0[ Surveys have shown that there has been a dramatic decrease in the weed~ora of _elds under rotational cultivation during the last 29 years[ This trend has been particularly noticeable in winter cereals\ a crop of increasing importance in the landscape[ 1[ The weed~ora of spring and winter cereals was compared in 08 unsprayed _elds during a 4!year study to test the hypothesis that cereal type exerts no e}ect on thẽ ora or on the absolute and relative abundance of single species[ 2[ Plant and species d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(44 citation statements)
references
References 7 publications
(10 reference statements)
3
39
0
Order By: Relevance
“…Roberts, 1984;Hald, 1999;Fried et al, 2008). Weed communities in rape crops (sown between August and October) were characterised by species preferentially emerging in autumn or late summer including Euphorbia helioscopia, Sinapis arvensis and Viola tricolor.…”
Section: Differences Among Annual Cropsmentioning
confidence: 99%
“…Roberts, 1984;Hald, 1999;Fried et al, 2008). Weed communities in rape crops (sown between August and October) were characterised by species preferentially emerging in autumn or late summer including Euphorbia helioscopia, Sinapis arvensis and Viola tricolor.…”
Section: Differences Among Annual Cropsmentioning
confidence: 99%
“…Over the course of the 20th century, synthetically produced herbicides and fertilizers radically changed the situation, enabling much more efficient weed control, more densely-planted and more competitive crops, and narrow rotations made up of just a few profitable crops. In cereal cultivation, shifts occurred from spring cereals towards winter cereals (Hald 1999a;Takács-György and Takács 2012), as well as towards earlier cultivation of cereal stubble . With the rise of chemical weed control, inversion tillage by means of ploughing was frequently replaced by reduced non-inversion tillage, or even no tillage (Chancellor, Fryer, and Cussans 1984;Cannell 1985;Morris et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys have shown that there has been a dramatic decrease in the weed density (Teasdale et al, 2004) and flora of fields under rotational cultivation (Hald, 1999). Effectiveness of a short-term management decision depends on the choice of the rotation and its elasticity patterns.…”
Section: Crop Rotation and Diversificationmentioning
confidence: 99%